Hydroxyapatite composited PEEK with 3D porous surface enhances osteoblast differentiation through mediating NO by macrophage. (16th December 2021) - Liu, Xingdan; Ouyang, Liping; Chen, Lan; Qiao, Yuqin; Ma, Xiaohan; Xu, Guohua; Liu, Xuanyong
Abstract: The adverse immune response mediated by macrophages is one of the main factors that are prone to lead poor osseointegration of polyetheretherketone (PEEK) implants in clinic. Hence, endowing PEEK with immunomodulatory ability to avoid the adverse immune response becomes a promising strategy to promote bone repair. In this work, sulfonation and hydrothermal treatment were used to fabricate a 3D porous surface on PEEK and hydroxyapatite (HA) composited PEEK. The HA composited PEEK with 3D porous surface inhibited macrophages polarizing to M1 phenotype and downregulated inducible nitric oxide synthase protein expression, which led to a nitric oxide concentration reduction in culture medium of mouse bone marrow mesenchymal stem cells (mBMSCs) under co-culture condition. The decrease of nitric oxide concentration could help to increase bone formation-related OSX and ALP genes expressions and decrease bone resorption-related MMP-9 and MMP-13 genes expressions via cAMP–PKA–RUNX2 pathway in mBMSCs. In summary, the HA composited PEEK with 3D porous surface has the potential to promote osteogenesis of PEEK through immunomodulation, which provides a promising strategy to improve the bone repair ability of PEEK.